EFEKTIVITAS PENANGANAN LUAS KAWASAN KUMUH PADA PROGRAM KOTAKU (KOTA TANPA KUMUH) DI KOTA JAYAPURA - Yulianti Liga Patubungan; Harmonis Rante; Bernathius Julison (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2022)
The KOTAKU (City Without Slums) program is a program for handling slum settlements into livable settlements, through increasing access to infrastructure. The implementation of the KOTAKU (City Without Slums) program in Jayapura City has been carried out from 2016 to 2021 in 8 Kelurahan. This study has 2 objectives, namely to analyze the effectiveness of the KOTAKU (City without Slums) program in reducing the area of slum settlements in Jayapura City by using 4 (four) variables, namely targeting accuracy, program socialization, program objectives and program monitoring and analyzing factors that affect achievement targets. The success of the KOTAKU (City Without Slums) program in reducing the area of slum settlements in Jayapura City. This study uses data analysis techniques that combine or link quantitative and qualitative research methods with data collection steps through observation, interviews and questionnaires. From the research carried out, conclusions have been obtained:(1) the average value of the percentage level of the effectiveness of the KOTAKU program in reducing the area of slum settlements in Jayapura City by using 4 (four) variables, the percentage is 70.79%. By referring to the Litbang Depdagri standard with a ratio of 60 – 79.99, the average level of program effectiveness is assessed as “Effective Enough”. (2) Factors Affecting Achievement Targets The success of the KOTAKU program in Reducing the Area of Slums in Jayapura City consists of supporting factors (human resources, budget and planning) and inhibiting factors (no budget collaboration, budget cuts, land location and impoverishment as well as related community mindsets projects and government grants)